2014
DOI: 10.1165/rcmb.2014-0018oc
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Regulates Epithelial Inflammation and Apoptosis by PolyI:C through Inhibition of Toll/IL-1 Receptor-Domain–Containing Adapter-Inducing IFN-β (TRIF) Recruitment to Toll-like Receptor 3

Abstract: MUC1/Muc1 (MUC1 in humans, Muc1 in animals) is a membrane-tethered mucin expressed by airway epithelial cells and plays an antiinflammatory role during airway bacterial infection. We previously demonstrated that MUC1/Muc1 is a negative regulator of Toll-like receptor (TLR) inflammatory signaling mediated through the myeloid differentiation primary response gene 88 (MyD88) adaptor protein. In the present study, we determined whether MUC1 regulates MyD88-independent TLR signaling mediated through the TLR3-Toll/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
0
25
0
1
Order By: Relevance
“…Binding of MUC1 to TLR5 in airway epithelial cells prevents the recruitment of MyD88 to the intracellular tail, thereby inhibiting signaling and NF-κB activation [47,96]. MUC1 also inhibits signaling through TLR3 [97] and dampens TLR2 and TLR5 signaling in ocular epithelial cells [98]. MUC1 is part of a feedback loop that downregulates TLR2-induced IL-8 and TNF-α production after infection with nontypeable Haemophilus influenzae in airway epithelial cells [99].…”
Section: Regulation Of Inflammatory Responses By Transmembrane Mucinsmentioning
confidence: 99%
“…Binding of MUC1 to TLR5 in airway epithelial cells prevents the recruitment of MyD88 to the intracellular tail, thereby inhibiting signaling and NF-κB activation [47,96]. MUC1 also inhibits signaling through TLR3 [97] and dampens TLR2 and TLR5 signaling in ocular epithelial cells [98]. MUC1 is part of a feedback loop that downregulates TLR2-induced IL-8 and TNF-α production after infection with nontypeable Haemophilus influenzae in airway epithelial cells [99].…”
Section: Regulation Of Inflammatory Responses By Transmembrane Mucinsmentioning
confidence: 99%
“…16 In addition, production of the antiinflammatory IL-10 and type I interferon (IFN) has been shown to correlate with increased MUC1 expression. [17][18][19] Investigations in mice with Helicobacter pylori-induced gastritis revealed that Muc1 expression negatively regulates the NLRP3 inflammasome, which mediates production of IL-1b. 20 Taken together, these data suggest that in addition to a barrier role to infection, MUC1 may also be involved with regulation of inflammation in response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…In gastric epithelia, MUC1 contributes to the physicochemical barrier against infectious pathogens (12). On airway epithelial cells, MUC1-EC is an adhesion site for Pseudomonas aeruginosa (Pa) (13,14), whereas MUC1-CT interacts with Toll-like receptors (TLRs) (15,16). Binding of MUC1-CT to TLR5 competitively inhibits recruitment of MyD88 to the TLR5 cytosolic Toll/IL-1 receptor domain, thereby suppressing TLR5 signaling and downstream inflammatory responses (15).…”
mentioning
confidence: 99%